(untitled) (Biological Sciences - PJSIR, 2009)
A new series of 4-[2’-(substituted phenyl)-5’-methoxy indolyl azetidine-1-yl/thiazolin-1-yl-3-(substituted phenyl)-5-mercapto-1,2,4-triazoles were designed, synthesized and tested for anti-inflammatory and analgesic activities. All compounds were screened in vitro for anti-inflammatory activity against carrageenan induced rat paw oedema and tested for their analgesic activity against phenyl quinone induced pain syndrome in mice at a dose of 50 mg/kg p.o. All the compounds of this series have been analyzed and confirmed by elemental (C, H, N) and spectral methods, i.e. I.R., 1H- NMR, 13C NMR and mass spectrometry data.